2020
DOI: 10.1088/1367-2630/ab60f1
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic graphene network loaded with Helmholtz resonators: a first-principle modeling, Dirac cones, edge and interface waves

Abstract: In this work, we study the propagation of sound waves in a honeycomb waveguide network loaded with Helmholtz resonators (HRs). By using a plane wave approximation in each waveguide we obtain a first-principle modeling of the network, which is an exact mapping to the graphene tight-binding Hamiltonian. We show that additional Dirac points appear in the band diagram when HRs are introduced at the network nodes. It allows to break the inversion (sub-lattice) symmetry by tuning the resonators, leading to the appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The correspondance between waveguides of alternating cross sections was already established and studied in [13], and also used to obtain two dimensional generalizations [16][17][18][19]. In such a setup, properties of the SSH model are directly realized in acoustics.…”
Section: From Acoustic Waveguides To the Su-schrieffer-heeger Modelmentioning
confidence: 99%
“…The correspondance between waveguides of alternating cross sections was already established and studied in [13], and also used to obtain two dimensional generalizations [16][17][18][19]. In such a setup, properties of the SSH model are directly realized in acoustics.…”
Section: From Acoustic Waveguides To the Su-schrieffer-heeger Modelmentioning
confidence: 99%
“…For this we consider a network of narrow air channels of equal length L but varying cross-sections. The typical transverse length ⊥ of the channels is assumed much smaller that its length L ( ⊥ L) so that inside each channel the propagation is monomodal [37][38][39]. In [30] it was shown that using cross-sections alternating between two values w and w , the system is described by an effective Hamiltonian that coincide with the 2D SSH model with hopping coefficients…”
Section: Acoustic Realisationmentioning
confidence: 99%
“…In this paper, we report on an acoustic SSH lattice model based on a different approach. The idea relies on considering acoustic waveguides made of segments of alternating cross sections but more importantly, equal lengths [19][20][21][22][23][24]. Starting from the 2D wave equation, for slender waveguide segments, we use a continuous monomode 1D approximation.…”
Section: Introductionmentioning
confidence: 99%